Mengukur Tingkat Kepuasan Pelanggan terhadap Pelayanan Biro Perjalanan Tamarind Wisata (Performance Importance Method) - Trias Septyoari Putranto; Raden Nana Kusdiana (Binus Business Review, 2013)
Research aims to measure the quality of service, and to measure customer satisfaction with the service Travel Bureau (BPW). It can thus be identified variable service according to the needs and expectations of customers as well as the variables that need improvement. Samples taken in this research were customers coming to the BPW office, with a sample size of 110 customers by random sampling of 50 customers. Method of analysis used was Importance-Performance Analysis.